Paisagens silenciosas: a invisibilidade do negro em Cerro Largo (RS) - Silva, Leandro Alexandre da (2017)
Cerro Largo is a town embedded at the interior of Rio Grande do Sul state, specifically at gaucho northwest, Missões Region. The region in question was one of the european immigration centers and Cerro Largo became a tipical german colonizated town. However, in 2010 IBGE verified and exposed contradictory data on this reality. It was identified the presence of 20% of black and brown citizens at the city’s urban area. In other words, at a german’s town, one fifth of the citizens are black colour. Such confirmation caused astonishment, once this contingent wasn’t verified on various city’s surroundings, at least not on this proportion. It seems that the black citizens in Cerro Largo live invisible, at a “nowhere”. That so, the goal of this study is – understand the construction of this “nowhere”, as well as the causes of this invisibility. Analyzing the data, documents and bibliographic reports on History and ethical matters of the city, employing etnographic techiques and discussion analysis, it is concluded that the teuto-brazilian comunity become hegemonic, isolating and excluding the called “brazilians”. Such isolation and exclusion are explained by historical factors, but also racialist factors. As time passed by certain values were associated to the so called “germans” and it’s culture while others were neglated to the “brazilians”. To the black people, living a more serious situation of exclusion, a whole of derogatory values were imprint, making them unworthy of participating of social life on this city. They live invisible, occupying the worst places and positions on “nowhere”. Over this situation hangs silence, that contributes even more to invisibilized the black citizens from Cerro Largo. Anyway, it was verified that the main characteristics of the coloured people’s “nowhere” at Cerro Largo is silence, invisibility and exclusion. Such factors are negation’s corollaries of a series of rights that end up configuring an almost-citizenship situation of this populational contingent. Therefore, this study is concluded suggesting public politics and confirmatory actions to give voice to the silenced, make visible the invisible ones and, finally, include them in citizenship. It is belived that the acknowlegment of fundamental rights is indispensable on the architecture of a more democratic and multicultured future for every Cerro Largo citizen